Blockchain as a Legal Compliance Infrastructure: Reinventing Corporate Governance and Internal Control Systems - Victor Chinedu Achebe,; Oluwatosin Ilori,; Ngozi Joan Isibor, (International Journal of Scientific Research in Science and Technology, 2024)
As organizations face increasing regulatory complexity and demand for transparency, blockchain technology is emerging as a transformative legal compliance infrastructure capable of redefining corporate governance and internal control systems. Blockchain’s core attributes immutability, decentralization, and real-time auditability offer a robust framework for enhancing accountability, ensuring data integrity, and automating compliance processes. This explores how blockchain can serve as an integrated tool for legal compliance, enabling organizations to build transparent, tamper-resistant systems that reinforce internal controls and promote stakeholder trust. The study begins by examining the limitations of traditional governance and compliance frameworks, which often suffer from fragmented data systems, manual oversight processes, and vulnerabilities to fraud and manipulation. It then analyzes blockchain’s potential to address these shortcomings by offering a single source of truth across organizational and regulatory boundaries. Smart contracts, in particular, are highlighted for their ability to automate compliance with legal and regulatory requirements, reducing human error and enforcement costs. This also investigates the broader implications for corporate governance, including enhanced board oversight, transparent voting mechanisms, and improved shareholder engagement. Legal and regulatory considerations are addressed, including jurisdictional issues, data privacy compliance (e.g., GDPR), and the legal recognition of blockchain-based records and contracts. Challenges such as scalability, interoperability, and ethical concerns related to surveillance and decentralization are critically examined. Finally, this provides strategic recommendations for businesses and policymakers, emphasizing the need for adaptive regulatory frameworks, cross-sector collaboration, and investment in blockchain education and infrastructure. As the technology matures, blockchain is poised to become a foundational layer for compliant, efficient, and trustworthy corporate ecosystems.
Keywords: Blockchain; Legal compliance; Infrastructure; Reinventing corporate; Governance; Internal control systems